Inclusive Education in Higher Education: The Perspective of Lecturer - Ashar, Muhammad Nurul; Wijiastuti, Asri; Ainin, Ima Kurrotun; Evans, David (Department of Special Education, 2023)
This study examined lecturers' perspectives regarding the practice of inclusive education. The quantitative study design with survey was applied. Respondents were selected through purposive sampling technique. A total of 30 lecturers who teach students with disabilities from one university were selected to complete the online survey. The survey questions were developed based on the concept of inclusive education’s implementation that have gone through a validity and reliability testing. Data were analyzed using simple statistics by calculating the percentage. Findings on the curriculum show that the majority of lecturers support the adoption and flexibility on curriculum. Similarly, they support the regulation and management themes as well as the support system, albeit improvements are required. Meanwhile, on the collaboration theme, majority of them showed an optimistic responses. Findings from this should enforce the continuous improvement on inclusive education practice in higher education.